PENERAPAN E-MODUL BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR KALKULUS INTEGRAL LIPAT - Venty Meilasari (Universitas Muhammadiyah Kotabumi, 2022)
Abstract: This research aims to improve learning outcomes of folding integral calculus. This research is Action Research. In one action cycle there are four stages, namely planning, implementing, observing, and reflecting. The research subjects were students in the fifth semester of the 2021/2022 academic year, the Mathematics Education Study Program, FKIP UMKO. The instruments in this study were tests, validation questionnaires, and observation sheets. The research was conducted in two cycles. Cycle 1 was declared not successful, because only 34% of students had achieved the target set. After making improvements based on the reflection results of cycle 1, cycle 2 was carried out. In cycle 2, it was found that 72% of students had achieved the set targets. Keywords: e-module, geogebra, folding integral calculus